Field-Scale Co-fermentation of Solid Waste From Urine-Diverting Dry Toilets (UDDT-SW) and Banana Waste to Produce Undissociated Carboxylic Acids to Inactivate Ascaris Eggs - Harroff, Lauren A.; Liotta, Janice L.; Wangolo, Emily E.; Egan, Tim J. S.; Bowman, Dwight D.; Angenent, Largus T. (Frontiers in Environmental Science, 2019)
Innovative, low-cost methods for inactivating pathogens in human fecal material (HFM) are needed, particularly in expanding urban areas where conventional sewer systems and centralized wastewater treatment plants are not feasible. To address this challenge, we have developed a bioprocess that utilizes open cultures of anaerobic bacteria (i.e., microbiomes) to produce carboxylic acids using HFM as substrate. When the pH is sufficiently low, the carboxylic acids exist in the undissociated form and inactivate pathogens. Here, we used real sanitation waste collected from container-based, urine-diverting dry toilets (UDDT-SW) in Nairobi, Kenya to conduct lab-scale and field-scale trials. Through these trials, we investigated operating conditions required to use carboxylic acid fermentation in sanitation waste treatment processes. We tested three different inoculum treatments and determined that the microbiome in UDDT-SW is well suited to produce carboxylic acids without the need for an external inoculum. We also tested co-fermentation of UDDT-SW with carbohydrate-rich food waste as a means of reducing the pH. We found that when food waste was incorporated in a way that maintained the pH between 4.8 and 5.2, then the food waste was quickly converted to carboxylic acids, and the low pH created high concentrations of undissociated carboxylic acids. The resulting concentrations of undissociated carboxylic acids resulted in Ascaris inactivation within 15 days. However, we found that a temperature ≥30°C is required for carboxylic acid production to occur.